Edukasi Penanganan Adiksi Remaja di Sekolah Melalui Pendekatan Kesehatan dan Agama - Yanuar Fahrizal; Fahmi Irfanudin; Syahruramdhani Syahruramdhani (Universitas Mathla'ul Anwar Banten, 2019)
EDUCATION OF ADOLESCENT ADDICTION TREATMENT WITH HEALTH AND RELIGIOUS EDUCATION APPROACHES AT SCHOOL. Smoking, drugs, pornography and video game addiction cases are iceberg mountain phenomenon which the cases are seen only as small part from fully part of the cases particularly in adolescent. This effects to health status of adolescent involve physics, mental, spiritual and social. Smoking, drugs, pornography and video game behaviour as abnormal behaviour on adolescent are an immature response from stress that happened in developing phase of adolescent. As the effort to prevent the incidence of adolescent abnormal behaviour and to increase mental health promotion especially on adolescent and teachers is needed preventive and pro-motive program with adolescent addiction education program. This program was conducted to teachers of MTs Muhammadiyah Kasihan because the teachers have much interaction with adolescent. This community service program was conducted with various method such as screening, preparation, teaching, empowering and evaluation. The result showed that the rate of teacher’s knowledge before conducting the education program is low or bad with score 48.1 and after conducting the education program increased to fair or enough with score 61.45. This community service program also developed module book about adolescent addiction treatment with health and religious education approaches.